PENGATURAN BATAS WAKTU PENDAFTARAN JAMINAN FIDUSIA PADA UNDANG-UNDANG NOMOR 42 TAHUN 1999 - Sarjana, I Gede Prima Praja (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 1 (2014)DO - 10.24843/JMHU.2014.v03.i01.p13, 2014)
This article have title is “The Arrangement of Time Limit of Registration of Fiducia Guarantee in the law number 42 in 1999 on fiducia guarantee”. The issue in this article on how is Arrangement of Time Limit of Registration of Fiducia Guarantee in the law number 42 in 1999 on fiducia guarantee. This study is normative law research. That is law research that based on secondary data (literature data). The approach have been applied in this study were statue approach that is the law number 42 in 1999 on fiducia guarantee, fact approach, and analytic and conceptual approach. Then analysis technique was by using descriptive, interpretation and argumentation. The result showed, first: the law number 42 in 1999 on fiducia guarantee start from article 11 until 18. it is not clearly describe on time limit of registration of fiducia guarantee, so that it can arise uncertainty of law. Recommendation can be submitted that in order to demand of law certainty, orderliness, and useful in order to protect the public as user of fiducia guarantee institution, hence limit time of registration of fiducia guarantee need to be arranged strickly in the Law number 42 in 1999 on fiducia guarantee
Keywords: Arrangement of time limit, registration of fiduci, fiducia guarantees